Genetic Association in the Maintenance of the Mitochondrial Microenvironment and Sperm Capacity - Thomas, Hwang I S; Chen, Ying-Shiuan; Hung, Ching-Han; Sreerangaraja Urs, Dilip Bhargava; Liao, Tien-Ling; Lai, Yen-Chun; Komrskova, Katerina; Postlerová, Pavla; Lin, Yung-Feng; Kao, Shu-Huei (Oxidative medicine and cellular longevity, 2021)
Sperm motility is one of the major determinants of male fertility. Since sperm need a great deal of energy to support their fast movement by active metabolism, they are thus extremely vulnerable to oxidative damage by the reactive oxygen species (ROS) and other free radicals generated as byproducts in the electron transport chain. The present study is aimed at understanding the impact of a mitochondrial oxidizing/reducing microenvironment in the etiopathology of male infertility. We detected the mitochondrial DNA (mtDNA) 4,977 bp deletion in human sperm. We examined the gene mutation of ATP synthase 6 (ATPase6 m.T8993G) in ATP generation, the gene polymorphisms of uncoupling protein 2 (UCP2, G-866A) in the uncoupling of oxidative phosphorylation, the role of genes such as manganese superoxide dismutase (MnSOD, C47T) and catalase (CAT, C-262T) in the scavenging system in neutralizing reactive oxygen species, and the role of human 8-oxoguanine DNA glycosylase (hOGG1, C1245G) in 8-hydroxy-2'-deoxyguanosine (8-OHdG) repair. We found that the sperm with higher motility were found to have a higher mitochondrial membrane potential and mitochondrial bioenergetics. The genotype frequencies of UCP2 G-866A, MnSOD C47T, and CAT C-262T were found to be significantly different among the fertile subjects, the infertile subjects with more than 50% motility, and the infertile subjects with less than 50% motility. A higher prevalence of the mtDNA 4,977 bp deletion was found in the subjects with impaired sperm motility and fertility. Furthermore, we found that there were significant differences between the occurrences of the mtDNA 4,977 bp deletion and MnSOD (C47T) and hOGG1 (C1245G). In conclusion, the maintenance of the mitochondrial redox microenvironment and genome integrity is an important issue in sperm motility and fertility.
Keywords: uncoupling protein 2; superoxiddismutasa; DNA Glycosylases; mitochondrie; Infertility, Male; lidé; Sperm Motility; mužské pohlaví; Uncoupling Protein 2; peroxid vodíku; Oxidative Stress; DNA, Mitochondrial; membránový potenciál mitochondrií; polymorfismus genetický; DNA-glykosylasy; Superoxide Dismutase; Polymorphism, Genetic; Humans; mitochondriální DNA; frekvence genu; Mitochondria; mužská infertilita; motilita spermií; Gene Frequency; Membrane Potential, Mitochondrial; oxidační stres; Spermatozoa; Hydrogen Peroxide; spermie; Male